REPRESENTASI PEREMPUAN SEBAGAI TOKOH PROTAGONIS DALAM FILM HOROR THAGHUT - Arvin Afdhila Maabuat; Oky Oxcygentri; Khairul Arief Rahman (Bajang Institute, 2025)
This research aims to understand the portrayal of female characters in horror films, which often depict women as weak, oppressed, or only able to fight back after becoming ghosts. Such portrayals reinforce the stereotype that women serve merely as victims or decorative elements in stories. Therefore, it brings a refreshing change when a horror film features female characters who are heroic or capable of resistance without turning into supernatural beings. The reason behind this research is the researcher’s awareness that the controversy surrounding the film Thaghut tends to overlook its positive aspects, particularly the portrayal of it’s female character and the film’s original intention as a medium of religious preaching (dakwah). This study uses a qualitative method with Umberto Eco’s semiotic approach to interpret the significance of meaning within scenes and evaluate whether the depiction or labeling of the main female character aligns with the researcher's expectations. Based on interviews with person who involved in the film’s production, it was revealed that the screenwriter of Thaghut, Lele Laila, often presents female characters in heroic roles and male characters as antagonists. However, the controversy stemmed from the film’s untimely release. Thus, this study highlights the positive elements found in Thaghut, especially in it’s portrayal of women.